Case report of cerebral cystic echinococcosis in a 5-year-old child - Menschaert, Denis; Daron, Aurore; Frere, Julie (Frontiers in Tropical Diseases, 2023)
Cystic echinococcosis is a zoonosis caused by the larval form of the tapeworm Echinococcus Granulosus. It has a worldwide distribution but has an important economic and health burden in endemic areas. The most affected organs are the liver and the lungs. Cerebral involvement is relatively rare. This is a clinical situation of cerebral presentation in a 5-year-old female patient of Moroccan origin who was identified during the development of recurrent seizures. Currently, the diagnosis is based on radiological imaging in the context of anamnestic suspicion. Apart from the conclusions that can be drawn from the various case reports, there are no guidelines or randomized controlled trials that have compared the different management methods. Their absence can be deleterious for the outcome of the children. We present this clinical case to expand the existing ones and to assist clinicians in their therapeutic decisions while awaiting guidelines.